2015
DOI: 10.1002/14651858.cd010790.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy for retinopathy in sickle cell disease

Abstract: Our conclusions are based on the data from two trials conducted over 20 years ago. In the absence of further evidence, laser treatment for sickle cell disease-related retinopathy should be considered as a one of therapeutic options for preventing visual loss and vitreous haemorrhage. However, it does not appear to have a significant different effect on other clinical outcomes such as regression of proliferative sickle retinopathy and development of new ones. No evidence is available assessing efficacy in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 43 publications
0
39
0
1
Order By: Relevance
“…It is effective in reducing the incidence of loss of visual acuity as well as the incidence of vitreous hemorrhage. [64, 70, 71] One study of 21 eyes with PSR found complete regression in 24 of 28 sea fan lesions treated with scatter laser photocoagulation. [72] Others have found complete regression in 30.2% of treated eyes compared to 22.4% of untreated control eyes.…”
Section: Resultsmentioning
confidence: 99%
“…It is effective in reducing the incidence of loss of visual acuity as well as the incidence of vitreous hemorrhage. [64, 70, 71] One study of 21 eyes with PSR found complete regression in 24 of 28 sea fan lesions treated with scatter laser photocoagulation. [72] Others have found complete regression in 30.2% of treated eyes compared to 22.4% of untreated control eyes.…”
Section: Resultsmentioning
confidence: 99%
“…25 There have been three principal approaches for the use of LPC in PSR treatment: (1) specifically targeting feeder vessels of neovascular sea fans (now, largely abandoned); (2) sectoral laser to treat the (presumably) ischemic retina immediately surrounding the neovascular sea fan; or (3) circumferential laser to treat all of the ischemic retina, whether affected or not affected by sea fans (largely reserved for patients who are at risk for not returning for follow-up care). 10 The use of sectoral or circumferential scatter LPC in PSR patients may be supported by extrapolation from extensive studies demonstrating the successful use of panretinal laser photocoagulation (PRP) for the treatment of PDR in diabetic patients; clinical trials have demonstrated the clear benefit of PRP for high-risk PDR. 11 However, an equivalent benefit of scatter LPC has not yet been unequivocally demonstrated for patients with PSR.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, an equivalent benefit of scatter LPC has not yet been unequivocally demonstrated for patients with PSR. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations